2001
DOI: 10.1164/ajrccm.164.4.2011040
|View full text |Cite
|
Sign up to set email alerts
|

Trial of Roxithromycin in Subjects with Asthma and Serological Evidence of Infection withChlamydia pneumoniae

Abstract: An association has been reported between chronic infection with Chlamydia pneumoniae and the severity of asthma, and uncontrolled observations have suggested that treatment with antibiotics active against C. pneumoniae leads to an improvement in asthma control. We studied the effect of roxithromycin in subjects with asthma and immunoglobulin G (IgG) antibodies to C. pneumoniae > or = 1:64 and/or IgA antibodies > or = 1:16. A total of 232 subjects, from Australia, New Zealand, Italy, or Argentina, were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(98 citation statements)
references
References 26 publications
3
89
1
5
Order By: Relevance
“…There was a significant improvement in evening PEF by 6 weeks, but this was nonsignificant after 6 months' follow-up [49]. This was in direct contrast to a smaller study of KRAFT et al [48], who measured significant improvements in FEV1 only in asthmatics whose BAL fluid was PCR-positive for either M. pneumoniae or C. pneumoniae compared to PCR-negative subjects.…”
Section: Asthmacontrasting
confidence: 57%
See 2 more Smart Citations
“…There was a significant improvement in evening PEF by 6 weeks, but this was nonsignificant after 6 months' follow-up [49]. This was in direct contrast to a smaller study of KRAFT et al [48], who measured significant improvements in FEV1 only in asthmatics whose BAL fluid was PCR-positive for either M. pneumoniae or C. pneumoniae compared to PCR-negative subjects.…”
Section: Asthmacontrasting
confidence: 57%
“…Two studies have examined the effects of macrolide therapy in asthmatics with serological or PCR evidence of infection with Mycoplasma pneumoniae or Chlamydia pneumoniae. The largest study of BLACK et al [49] examined the effect of 6 weeks' roxithromycin or placebo treatment on 232 asthmatics with serological evidence of infection with C. pneumoniae. No significant change in the primary end-points of mean morning peak expiratory flow (PEF) or symptom score was observed.…”
Section: Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies have reported conflicting results [53][54][55][56][57]. Recently, SUTHERLAND et al [58] evaluated the effect of 16 weeks of either clarithromycin or placebo, added to fluticasone, on asthma control in individuals with or without lower airway PCR evidence of M. pneumoniae or C. pneumoniae.…”
Section: Asthmamentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26] A 2005 Cochrane review concluded that there was insufficient evidence to confirm or refute the role of macrolide treatment in chronic asthma. 1 Since 2005, 3 additional trials of macrolides in chronic adult asthma have reported patient-oriented outcomes.…”
Section: Previous Studiesmentioning
confidence: 99%